2022
DOI: 10.1159/000527881
|View full text |Cite
|
Sign up to set email alerts
|

What Kind of Patients Receive Inpatient and Day-Hospital Treatment in Departments of Psychosomatic Medicine and Psychotherapy in Germany?

Abstract: <b><i>Introduction:</i></b> Germany is one of the few countries with a medical specialty of psychosomatic medicine and psychotherapy and many treatment resources of this kind. <b><i>Objective:</i></b> This observational study describes the psychosomatic treatment programs as well as a large sample of day-hospital and inpatients in great detail using structured diagnostic interviews. <b><i>Methods:</i></b> Mental disorders were diagnosed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…At least one diagnosis of a concurrent somatic disorder occurred in 1,363 (65.1%) of the patients. More detailed information about diagnoses is given in Doering et al ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At least one diagnosis of a concurrent somatic disorder occurred in 1,363 (65.1%) of the patients. More detailed information about diagnoses is given in Doering et al ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the patient sample (n = 2,094) at baseline has already been published [21]. The patient flow chart is provided in Figure 1.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Возможна примесь слизи к фекалиям или даже выделение ее в виде клочьев, пленок. Иногда наблюдается проктомиксорея -приступообразное выделение слизи из прямой кишки [3,12,17,20,25].…”
Section: основные клинические проявленияunclassified
“…However, findings are restricted to naturalistic studies as the design of RCTs is impaired by methodological, pragmatic, and ethical reasons [38]. A prospective naturalistic study was initiated at 19 German university hospitals for psychosomatic medicine and psychotherapy, which included a total of 2,094 patients and is currently in final evaluation [39]. A previous systemic review and meta-analysis including 59 studies on inpatient treatment reported a medium within-group effect size for symptom change of d = 72.…”
Section: From Diagnostics To Therapymentioning
confidence: 99%